The effects of climate change on the flowering phenology of alder trees in southwestern Europe - Rojo, Jesús; Fernández-González, Federico; Lara, Beatriz; Bouso, Verónica; Crespo, Guillermo; Hernández-Palacios, Gonzalo; Rodríguez-Rojo, María Pilar; Rodríguez-Torres, Alfonso; Smith, Matt; Pérez-Badia, Rosa (Mediterranean Botany, 2021)
Global warming impacts plant phenology and the effect of climate change will be more intensely experienced at the edges of a plant's distribution. This work focuses on Iberian alder's climatic range (Alnus lusitanica Vít, Douda & Mandák). The Iberian Peninsula constitutes the Southwestern edge of the global chorological distribution of European black alder (Alnus glutinosa (L.) Gaertn. s.l.), and some of the warmest and driest conditions for the alder population are located in the center of Spain. The critical temperature-relevant periods that regulate the reproductive phenology of alder were analyzed using a statistical-based method for modeling chilling and forcing accumulation periods in temperate trees. Our results reveal that autumn chilling was the most important thermal accumulation period for alder in a Mediterranean climate while forcing requirements are satisfied in a short period of time. Autumn temperatures were significantly correlated with the timing of flowering, and chill units during this season directly influence start-dates of alder flowering. A positive trend was observed in pollen seasons' timing, meaning a slight delay of alder flowering in central Spain. It coincided with autumn warming during the period 2004-2018. If this warming trend continues, our results predict a delay in the start-date of flowering by around 3-days for every degree increase in maximum autumn temperatures according to the most optimistic emission scenarios.